Intervención educativa en el conocimiento y prácticas preventivas del COVID-19 en comerciantes de mercados Iquitos 2022 - Becerra Kahn de Vela, Marilin Marina (2025)
The study aimed to determine the effect of the educational intervention on the knowledge and practice of COVID-19 preventive measures among merchants from the Central, Belén, and Punchana markets in Iquitos, 2022. It was a quantitative study with a pre-experimental design, using a pre- and post-test with a single group. The sample consisted of 30 merchants. Techniques used included interviews, observation, workshops, educational sessions, and demonstrations. The instruments were: the COVID-19 questionnaire (95% validity and 93% reliability), the checklist of preventive practices against COVID-19 (96% validity and 94% reliability), and the educational intervention. The results showed that, regarding knowledge about COVID-19, 96.7% had incorrect knowledge before the intervention; after 15 and 30 days, 100% demonstrated correct knowledge. In terms of preventive practices, 30% performed inadequate practices before the intervention; afterward, 73.3% performed adequate practices at both 15 and 30 days, while 26.7% failed to improve. ANOVA analysis yielded a p-value of 0.000 for knowledge and practices, allowing the acceptance of the hypothesis: the educational intervention has statistically significant effects on knowledge and preventive practices against COVID-19 among merchants from the Central, Belén, and Punchana markets in Iquitos, 2022.It was concluded that the educational intervention was effective, and it is recommended to continue training merchants in the prevention of this disease.